The Effect of Toxic Leadership and Job Insecurity on Employee Turnover Intention with Job Satisfaction as a Mediation Variable at PT. XYZ Sidoarjo - Christiono, Naufal Akmal; Abadiyah, Rifdah; Adji, Kumara (Universitas Pamulang, 2026)
This study aims to analyze the influence of toxic leadership and job insecurity on employee turnover intention, with job satisfaction as a mediating variable at PT. XYZ in Sidoarjo. The high turnover rate indicates potential issues in human resource management. Reduced work satisfaction and increased desire to leave can be caused by destructive leadership styles and uncertainty surrounding employment continuation. This study used a causal research design and a quantitative methodology. Questionnaires were sent out to 99 people to gather data, which was then calculated using the Slovin formula and analyzed using the PLS-SEM approach with SmartPLS 4.0 software. Job satisfaction and desire to leave are greatly impacted by toxic leadership and job instability, according to the research. In addition, the impact of these factors on the intention to leave is moderated by work satisfaction. Companies may use these findings to improve leadership, increase job security, and build a more welcoming workplace, all of which should help them retain more employees.